The Tragedy of Public Housing: Spatial Analysis of Hotspots of Aggravated Assaults in Louisville, KY (1989–1998) - Suresh, Geetha (American journal of criminal justice, 2007)
In a community-level analysis, this study examines violent crime hot spots and displacement patterns in the city of Louisville, KY, from 1989 to 1998. Park DuValle, a neighborhood in Louisville, KY, was one of the major historic hot spots for assaults until 1998. The revitalization of the two vulnerable low-income public housing developments in Park DuValle, combined with the acquisition of nearby dilapidated and unattended private property by the Housing Authority of Louisville, caused a shift in the clustering pattern of assaults at Park DuValle in the 1997 and 1998. Maps revealed that assaults were displaced from the Park DuValle neighborhood to the Central Business District—the neighborhood where the majority of former residents of the Park DuValle public housing units were relocated. Both Park DuValle and the Center Business District were associated with low-income census blocks in Louisville, KY. These low-income public housing developments have exhibited a higher incidence of aggravated assaults. The results are discussed in the context of the possible revitalization of low-income public housing units. The study concludes that clustering and displacement of assault hot spots as well as emphasis on the decentralization of low-income residents need to be addressed further.